Do Hedonic or Utilitarian Types of Online Product Reviews Make Reviews More Helpful?: A New Approach to Understanding Customer Review Helpfulness on Amazon - Islam, Maidul; Kang, Mincheol; Haile, Tegegne Tesfaye (Journal of Global Information Management, 2021)
Online sales can be influenced significantly by customer reviews; thus, there are several studies on what makes an online review helpful to consumers. However, none of those researches address the review helpfulness in the context of hedonic and utilitarian review types. This study examines how product type (hedonic and utilitarian) moderates the relationship between the level of review type (hedonicity and utilitarianity) and review helpfulness. To test the moderating effects, customer review data for perfume and bar soap product was collected from Amazon.com and analyzed by using a text-mining tool (QDA Miner) and a structural equation modeling software (AMOS 22.0). The results of this study indicate that the product type moderates the impact of the review type on review helpfulness when product type and review type are incongruent. Further, results show that the number of sentences in a customer review affects the review helpfulness when product type is utilitarian.
Keywords: Amazon; Customer review; Hedonic; New approaches; Online product reviews; Product types; QDA miner; Review helpfulness; Review type; Utilitarian; Amazon; Customer Review; Hedonic; Product Type; QDA Miner; Review Helpfulness; Review Type; Utilitarian